2000
DOI: 10.1097/00000374-200007000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Inhibition: The Humoral and Cellular Immune Response to Hepatitis C Virus NS5 Protein After Genetic Immunization

Abstract: These results suggest that the high rate of chronic HCV infection in alcoholics may be due to ethanol's effects on antiviral immune responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…The immunosuppressive effects of ethanol have been extensively studied, and it has been shown that chronic ethanol consumption causes broad immunosuppression, such as reduction of the viral-specific-induced cytotoxic T-lymphocyte and naturalkiller activity. 25,26 Second, ethanol directly inhibits the IFN-␣-activated signals by p42/44MAP kinase and PKC-dependent mechanisms. 27 Third, chronic ethanol consumption inhibits IFN therapy by induction of a wide variety of cytokines, including tumor necrosis factor ␣ (TNF-␣), interleukin (IL)-1, IL-8, and IL-10.…”
Section: Discussionmentioning
confidence: 99%
“…The immunosuppressive effects of ethanol have been extensively studied, and it has been shown that chronic ethanol consumption causes broad immunosuppression, such as reduction of the viral-specific-induced cytotoxic T-lymphocyte and naturalkiller activity. 25,26 Second, ethanol directly inhibits the IFN-␣-activated signals by p42/44MAP kinase and PKC-dependent mechanisms. 27 Third, chronic ethanol consumption inhibits IFN therapy by induction of a wide variety of cytokines, including tumor necrosis factor ␣ (TNF-␣), interleukin (IL)-1, IL-8, and IL-10.…”
Section: Discussionmentioning
confidence: 99%
“…These observations were recapitulated in several animal studies. For instance, mice chronically exposed to ethanol generate reduced CD4 and CD8 T cell responses, with diminished proliferation, cytotoxicity and T-helper 1 (Th1) cytokine production following immunization with HCV antigen [3,4]. Similarly, chronic ethanol exposure also results in ablated CD8 T cell responses and a shift to Th2 responses in mice following infection with Listeria monocytogenes [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Longterm ethanol ingestion may broadly influence immunity (5,6). Previous experimental studies suggest that CD4 1 T cell proliferation and cytotoxic T-lymphocyte (CTL) activity responses to NS5 or hepatitis C virus (HCV) core proteins were suppressed by chronic ethanol consump-tion (3,7,8). Further investigations reveal that viral antigen specific impairment of CD4 1 T cell proliferation and CTL activity may be restored by interleukin (IL)-2 and granulocyte-macrophage colony-stimulating factor additions (7,8).…”
Section: Introductionmentioning
confidence: 99%